Assessment of Scour Depth Downstream of Sharp Crested Weirs: An Experimental Study - Israa A. Mohammed Jawad; Thamer Ahmad Mohammad (Journal of Engineering)
Weirs are hydraulic structures built across open channels to measure the flow and raise the water level. A sharp-crested weir is one type of weir of different configurations. Local scour at the downstream of hydraulic structures is a problem that affects their safety and stability. The credibility of the estimation of maximum scour depth is debated in many published studies. In this study, an experimental work was conducted to investigate the impact of flow rates on maximum scour depth downstream of a sharp-crested weir. The weir model was calibrated before it was used in the discharge measurement. The value of the weir coefficient of discharge was found to be 0.633. The experiments were conducted on a plexiglass model of a sharp crested weir, which was tightly fixed at the middle of a laboratory flume. The weir had a crest height of 15 cm above the flume bed. In the experiments, a non-uniform sediment was used with a median diameter (d50) of 0.72 mm; it was placed downstream of the weir within the working section at a depth of 6.5 cm. The scour depths at an interval of 4 cm were measured by a point gauge. The measurement covered the resulting scour hole. The maximum recorded scour depth of 6.2 cm was observed approximately at the center of the flume width, with a Froude number of 0.0313. The measured maximum scour depths were found to agree with those published by other studies.